ASSESSMENT OF PRESCRIPTIONS BASED ON ADMINISTRATIVE ASPECTS IN HYPERTENSIVE PATIENTS AT THE GARUT DEVELOPMENT HEALTH CENTER - Dani Sujana, Dani Sujana; Yoga Trisyan, Yoga Trisyan (Jurnal Medika Farmaka, 2023)
Prescription review is the process of checking prescriptions for the first time after the prescription is received. Prescriptions based on administrative aspects are the initial screening when prescriptions are served which aims to analyze any problems related to treatment so as to minimize the occurrence of medication errors in prescriptions. This study aims to examine the administrative completeness of prescriptions at the Garut City Development Health Center. The data was taken primary or the latest data as many as 223 recipes. The results showed that the administrative completeness of the prescription included prescription date 100, patient name 100 age 100percent, gender 100percent, address 100, weight 0%, doctor’s name 35.1percent prescription 55.1percent doctor’s initials 0. Based on the results of the study, then it can be concluded that the prescriptions studied at the Garut City Development Health Center have incomplete prescriptions based on the Minister of Health Regulation no.74 of 2016 concerning pharmaceutical Service Standards in Puskesmas.